2022
DOI: 10.3390/cimb44070197
|View full text |Cite
|
Sign up to set email alerts
|

Is Aberrant DNA Methylation a Key Factor in Molar Incisor Hypomineralization?

Abstract: Molar incisor hypomineralization (MIH) is a qualitative disturbance of the enamel of the permanent molars and/or incisors. Its etiology is not clearly defined but is connected with different factors occurring before and after birth. It remains difficult to identify a single factor or group of factors, and the problem is further complicated by various overlapping mechanisms. In this study, we attempted to determine whether DNA methylation—an epigenetic mechanism—plays a key role in the etiology of MIH. We colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The results showed no prominent difference between children with MIH and healthy group. However, significant differences in global DNA methylation levels were connected with five potential factors (number of pregnancies, number of births, type of delivery, varicella infection, and high fever [under 3 years old]) for MIH development (Tynior et al, 2022). Silva MJ et al collected umbilical cord blood from 27 pairs of twins and performed genome‐wide DNA methylation analysis, and examined their oral conditions at the age of 6.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed no prominent difference between children with MIH and healthy group. However, significant differences in global DNA methylation levels were connected with five potential factors (number of pregnancies, number of births, type of delivery, varicella infection, and high fever [under 3 years old]) for MIH development (Tynior et al, 2022). Silva MJ et al collected umbilical cord blood from 27 pairs of twins and performed genome‐wide DNA methylation analysis, and examined their oral conditions at the age of 6.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies directly explored on samples from human body. Wojciech Tynior et al collected buccal mucosa swabs to test global DNA methylation levels (Tynior et al, 2022). And Silva MJ et al performed genome‐wide DNA methylation analysis collecting umbilical cord blood (Mj et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One twin study, suggesting multiple genes known to be associated with tooth formation, showed differential methylation in children with dental caries and hypomineralized second primary molars [ 107 ]. A study using cheek cells found no difference in global methylation of DNA in children with MH [ 108 ]. While these epigenetic studies are quite preliminary, collectively, they suggest the potential contribution of epigenetics to DDE either as an association, or possibly mechanistically, by altering the expression of genes important to normal enamel development.…”
Section: Gene and Environment Interactions Influencing Enamel Develop...mentioning
confidence: 99%